2018
DOI: 10.1016/j.jrp.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

The role of vigilance in the relationship between neuroticism and health: A registered report

Abstract: The theory of healthy neuroticism, that neuroticism can impact health through both negative and positive pathways, often relies on descriptions of vigilance to illustrate beneficial effects. The current study is among the first to describe the relationship of neuroticism to body vigilance and test the degree to which this relationship impacts health. In an online participant panel (N = 1055), neuroticism was associated with one factor of vigilance: sensation awareness belief. This factor had a suppression effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 59 publications
1
27
2
Order By: Relevance
“…This explanation is consistent with a recent study in which the authors found that the neuroticism variation that overlapped with "bodily vigilance", which was measured by questions such as "How much do you wonder about why your body feels the way it does? ", was associated with better health, and that the other neuroticism variance was related to poorer health (Weston & Jackson, 2018). It is also consistent with earlier reports that people high in neuroticism tend to report symptoms more frequently even if there is no underlying disease (Costa & McCrae, 1987) and seek medical attention more often (B. Friedman, Veazie, Chapman, Manning, & Duberstein, 2013), and so these individuals may be more likely to be diagnosed and treated at earlier stages of a disease process (H. S. Friedman, 2019).…”
Section: Discussionsupporting
confidence: 88%
“…This explanation is consistent with a recent study in which the authors found that the neuroticism variation that overlapped with "bodily vigilance", which was measured by questions such as "How much do you wonder about why your body feels the way it does? ", was associated with better health, and that the other neuroticism variance was related to poorer health (Weston & Jackson, 2018). It is also consistent with earlier reports that people high in neuroticism tend to report symptoms more frequently even if there is no underlying disease (Costa & McCrae, 1987) and seek medical attention more often (B. Friedman, Veazie, Chapman, Manning, & Duberstein, 2013), and so these individuals may be more likely to be diagnosed and treated at earlier stages of a disease process (H. S. Friedman, 2019).…”
Section: Discussionsupporting
confidence: 88%
“…Given that people with interpersonal vulnerabilities are inclined to be more reactive, vigilant, and insecure (e.g. Ravary & Baldwin, 2018; Suls & Martin, 2005; Wei et al, 2005; Weston & Jackson, 2018), we see interpersonal vulnerabilities as predictors of lower average levels and higher within‐person variability of beneficial relationship components. The lower levels and higher variability are considered to mediate selection effects between interpersonal vulnerabilities (i.e.…”
Section: The Present Studymentioning
confidence: 95%
“…Given that people with interpersonal vulnerabilities are inclined to be more reactive, vigilant, and insecure (e.g. Ravary & Baldwin, 2018;Suls & Martin, 2005;Wei et al, 2005;Weston & Jackson, 2018), we see interpersonal vulnerabilities as predictors of lower average levels and higher within-person variability of beneficial relationship components. The lower levels and higher variability are considered to mediate selection effects between interpersonal vulnerabilities (i.e.…”
Section: Selection Effectsmentioning
confidence: 92%